Complete mitochondrial genome of Cygnus olor (Aves, Anseriformes, Anatidae). (2nd September 2016) - Park, Chang Eon; Park, Gun-Seok; Kwak, Yunyoung; Hong, Sung-Jun; Khan, Abdur Rahim; Jung, Byung Kwon; Park, Yeong-Jun; Kim, Jong-Guk; Park, Hee Cheon; Shin, Jae-Ho
Abstract: The complete mitochondrial genome of Cygnus olor (Aves, Anseriformes, Anatidae) was revealed in this study. Total 16 739 base pairs (bp) of this mitogenome encoded genes for 13 protein coding genes (PCGs), two ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and a D-loop (control region). The 12S rRNA and 16S rRNA genes are located between tRNA-Phe and tRNA-Leu (UUR) and segmentalized by the tRNA-Val. D-loop is located between tRNA-Glu and tRNA-Phe. The overall base composition of C. olor is G + C: 47.8%, A + T: 52.2%, apparently with a slight AT bias. Following the phylogenetic analysis, the C. olor was closed to Anser cygnoides .